Prevalence study of Mycoplasma synoviae in broiler flocks with lameness in Shahrekord and Isfahan, Iran - FATHI-HAFSHEJANI, EZATOLLAH; GHOLAMI-AHANGARAN, MAJID; NASEH-FAR, ARMAN (The Indian Journal of Animal Sciences, 2016)
Identification of Mycoplasma synoviae (M. synoviae), an economically important pathogen in poultry industries worldwide, in clinical samples has critical importance. This study was conducted to determine the prevalence of M. synoviae in broiler flocks with clinical lameness using serological and polymerase chain reaction (PCR) methods. Blood serum samples (200) and joint fluid samples (200) were collected from 20 broiler flocks. All serum samples were studied using the serum plate agglutination (SPA) test while all joint fluid samples were studied using the PCR technique for detection of vIhA gene of M. synoviae. Results showed that 61 serum samples from 11 broiler flocks were positive for SPA test while 42 out of 61 samples were positive using SPA with 1/2 dilution. The PCR method indicated that 102 joint fluid samples of 16 broiler flocks were positive for presence of the vIhA gene of M. synoviae. Our results showed that the SPA and PCR techniques can be used for determination of the prevalence of M. synoviae in clinical samples of poultry.